Methodologies, Knowledge Areas and Tourist Destinations Addressed in Scientific Research on Tourism Induced by Audiovisual Fiction (1988-2021) - María C. Puche-Ruiz; Esmeralda Crespo-Almendros; Sebastián Sánchez-Castillo (Profesional de la información, 2024)
This article analyses the methodological evolution experienced in academic research on the phenomenon of tourism induced first by the cinema and later by the audiovisual media in general during the period 1988-2021. Emphasis is placed on the methodological techniques employed and the tourist destinations considered from the perspective of marketing, communication and tourism studies. By means of a systematised analysis, 354 articles from the Scopus, WOS and Journal Citation Report databases were reviewed. The results suggest the existence of two main lines of analysis: conceptual theory (cultural geography and communication) and empirical analysis (analysis of specific products by marketing experts). Descriptive and quantitative analyses were found to be in the majority as opposed to causal and qualitative analyses. The predominance of researchers from the Anglo-Saxon and Asian spheres, who study the phenomenon of film-induced tourism within their borders, has been discovered.